Investment Complementarities, Coordination Failure and Systemic Bankruptcy - Mei Li (Queen's University, Department of Economics, 2007)
I argue that systemic bankruptcy of firms can originate from coordination failure in an economy with investment complementarities. This new explanation about the origin of systemic bankruptcy promotes better understanding of how financial fragility arises, and provides theoretical guidance for central banks to establish an "early warning system" to prevent the occurrence of financial crises. In a global game setup, investment decisions of firms are studied in the presence of uncertainty and investment complementarities. Uncertainty is twofold here: first, firms are uncertain about economic fundamentals; second, firms are also uncertain about other firms' investment decisions. I demonstrate that even small uncertainty about economic fundamentals can be magnified through the uncertainty about other firms' investment decisions and can lead to coordination failure, which may be manifested as systemic bankruptcy. Moreover, my model reveals that systemic bankruptcy tends to arise when economic fundamentals are in the middle range where coordination matters. High financial leverage of firms greatly increases the severity of systemic bankruptcy. Optimistic beliefs of firms and banks can alleviate coordination failure, but can also increase the severity of systemic bankruptcy once it happens.
Keywords: D82; E44; G21; 330; Systemic Bankruptcy; Financial Crises; Global Games; Investitionsentscheidung; Entscheidung unter Unsicherheit; Koordination; Unternehmenserfolg; Finanzkrise; Insolvenz; Theorie